(untitled) (Kronika Bydgoska, 2016)
In the years preceding the outbreak of World War II, the state authorities, being aware of the weaknesses of the Polish Army, wanted to strengthen it in various ways. One of them was special funds established for the purposes of fundraising and collection of goods. The most active of them included the National Defense Fund, the Marine Defense Fund, and the Anti-Aircraft Defense Loan. Bydgoszcz residents had quickly joined all activities. Money and contributions in kind were donated by many workplaces, factories and enterprises, as well as social and political organizations, and private individuals. Based on sources and press publications we know that residents of Bydgoszcz contributed generously to these collections. They were also involved in “live torpedo” campaigns and the “Legion to Liberate Gdańsk.”